Microsaccade-induced prolongation of saccade latencies depends on microsaccade amplitude - Martin Rolfs; Jochen Laubrock; Reinhold Kliegl (Journal of Eye Movement Research)
Fixations consist of small movements including microsaccades, i.e., rapid flicks in eye position that replace the retinal image by up to 1 degree of visual angle. Recently, we showed in a delayed-saccade task (1) that the rate of microsaccades decreased in the course of saccade preparation and (2) that microsaccades occurring around the time of a go signal were associated with prolonged saccade latencies (Rolfs et al., 2006). A re-analysis of the same data set revealed a strong dependence of these findings on microsaccade amplitude. First, microsaccade amplitude dropped to a minimum just before the generation of a saccade. Second, the delay of response saccades was a function of microsaccade amplitude: Microsaccades with larger amplitudes were followed by longer response latencies. These finding were predicted by a recently proposed model that attributes microsaccade generation to fixation-related activity in a saccadic motor map that is in competition with the generation of large saccades (Rolfs et al., 2008). We propose, therefore, that microsaccade statistics provide a behavioral correlate of fixation-related activity in the oculomotor system.